2-Chloro-N′-(4-nitrobenzylidene)benzohydrazide - Zhou, Cong-Shan (International Union of Crystallography, 2010)
The title Schiff base compound, C(14)H(10)ClN(3)O(3), exists in a trans configuration with respect to the C=N bond. The dihedral angle between the two benzene rings is 15.9 (2)°. In the crystal, the molecules are linked into chains along [101] by intermolecular N—H⋯O hydrogen bonds.